2013
DOI: 10.3892/or.2013.2350
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid negatively affects the expansion of in vitro activated human NK cells and their cytolytic interactions with Ewing sarcoma cells

Abstract: Abstract. Disseminated Ewing sarcoma remains a fatal disease despite advanced multimodal treatment regimens. Immunotherapies as well as novel drugs and biologicals are currently being explored to eliminate minimal residual disease after conventional therapy thereby rescuing patients at a high risk for relapse. Insights into the interactions between novel therapies provide the basis for the development of effective combination strategies. We investigated the effects of the aminobisphosphonate zoledronic acid (Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…CD57 is frequently used to detect NK cells in human tissue, which have been recognized to have anti-tumoral properties, including increased survival time, in various malignancies (37)(38)(39). This is consistent with the hypothesis that increased stromal Fer expression is associated with decreased malignant potential and improved prognosis in RCC.…”
Section: Stromal Fer Expression -------------------------------------supporting
confidence: 64%
“…CD57 is frequently used to detect NK cells in human tissue, which have been recognized to have anti-tumoral properties, including increased survival time, in various malignancies (37)(38)(39). This is consistent with the hypothesis that increased stromal Fer expression is associated with decreased malignant potential and improved prognosis in RCC.…”
Section: Stromal Fer Expression -------------------------------------supporting
confidence: 64%
“…In contrast, one study investigating the in vitro effects of ZOL on NK cells from healthy donors and Ewing sarcoma patients found that ZOL significantly impaired expansion of NK cells. In this study, ZOL impaired the degranulation response of NK cells to Ewing sarcoma stimulus suggesting a decrease in functional activity in which ZOL may help increase the survival of tumour cells in this context [93] .…”
Section: Evidence From Pre-clinical Studiesmentioning
confidence: 51%
“…With a peak of incidence at the age of 45 years, chondrosarcoma is a cartilaginous tumor characterized by malignant chondrocytes trapped in a poorly-vascularized hyaline-like extracellular matrix [95]. Depending on the histological subtype, chondrosarcomas are associated with somatic mutations in IDH-1 or IDH-2, EXT, p53, Rb, or COL2A1.…”
Section: Bps In the Treatment Of Chondrosarcomamentioning
confidence: 99%